2007
DOI: 10.1056/nejmoa070844
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Influenza Vaccine in the Community-Dwelling Elderly

Abstract: During 10 seasons, influenza vaccination was associated with significant reductions in the risk of hospitalization for pneumonia or influenza and in the risk of death among community-dwelling elderly persons. Vaccine delivery to this high-priority group should be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
329
5
14

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(356 citation statements)
references
References 41 publications
8
329
5
14
Order By: Relevance
“…The effectiveness of inactivated influenza virus vaccine has been confirmed in several studies among all age groups [4][5][6]. Furthermore, vaccination has been shown to be both cost-efficient and cost-saving [7][8][9]. Children experience high attack rates that may reach 40% of the general pediatric population during annual influenza epidemics [10].…”
Section: Introductionmentioning
confidence: 96%
“…The effectiveness of inactivated influenza virus vaccine has been confirmed in several studies among all age groups [4][5][6]. Furthermore, vaccination has been shown to be both cost-efficient and cost-saving [7][8][9]. Children experience high attack rates that may reach 40% of the general pediatric population during annual influenza epidemics [10].…”
Section: Introductionmentioning
confidence: 96%
“…Notably, in contrast, adult vaccination decreases mortality and morbidity linked to vaccine-preventable diseases 139 as well as is associated with reduced use of antibiotics and a decrease in antibioticresistant infections. 140,141 Table 2 summarizes recommendations on vaccination for adults and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the reduction in hospitalization and mortality rates observed among vaccinated patients, the overall effectiveness of vaccination in the elderly is uncertain 17 . A large, randomized, controlled trial using vaccinated subjects slightly older and with higher prevalence rates of all the baseline medical conditions except dementia or stroke, found that vaccination for seasonal flu was associated with a 27% reduction in the risk of hospitalization for pneumonia or influenza (adjusted odds ratio, 0.73; 95% confidence interval [CI], 0.68 to 0.77) and a 48% reduction in the risk of death (adjusted odds ratio, 0.52; 95% CI, 0.50 to 0.55) 23 . Reliable estimates of the benefits of vaccination are important for establishing informed policies regarding resource allocation for the immunizations and identifying the need for new vaccines and strategies for the prevention and control of influenza in this group.…”
Section: Discussionmentioning
confidence: 99%